UK and France: Friends or Foes? (Trans) cultural and legal unions and disunions - Gadbin-George, Gibson-Morgan, Geraldine, Elizabeth; Gadbin-George, Gibson-Morgan, Geraldine, Elizabeth (Editions Le Manuscrit, 2019)
At a time of major changes in the United Kingdom and to a lesser extent in France, induced by the proposed Brexit process, this collective work composed of thirteen chapters from highly experienced academics and specialist professionals from both sides of the Channel examines their consequences on the French and British relationship in a range of institutional, political, legal, economic, cultural but also strategic and defence-related fields with an emphasis on comparative and/or European points of view. The two editors are respectively Associate Professors at Panthéon-Assas and Tours universities. Geraldine Gadbin-George is an English solicitor, a former avocat at the Paris bar and a former French judge. Elizabeth Gibson-Morgan is Visiting Senior Research Fellow at King's College London in the Department of Contemporary History.